DESIGN AND DEVELOPMENT APPLICATION OF ACADEMIC GRADE FOR STUDENT BASED ON WEB AT SMAK ST.CLEMENS BOAWAE FLORES - deta, Bernadete; Sulistiowati, Sulistiowati; Soebijono, Tony (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
St. Clemens Christian High School is a private education institute Binawirawan Foundation owned by the nuns of Congregation Imitationis Jesus (CIJ) at Trans Bajawa-Ende km 40 Boawae. St. Clemens Christian High School (SMACEL) has 3 (three) majors, that are Science, Social, and Language. SMACEL now is working at processing of academic grade using 2013’s curriculum. Every subject there is a grouping process for grade type, there are daily grade, task grade, and final exam grade. The second type of grade is skill grade, composed by practice, project, and portopholio grade. The grade of attitude composed by spiritual and good attitude grade. The problem that has been experienced nowadays for processing the grades are the entry of grades, the presentation of report, and data information. The report process now is managed by Microsoft Office and Excel and the retyping of reports is necessary so it takes a long time and slowing down the distribution of reports.And the solution for academic administration is to develop an application for academic grade processing at SMACEL Boawae Flores. The application is web-based so that can be accessed at wherever places with the internet access.The academic processing grade application is being tested for inputing the student’s grade and hope to help the academic curriculum department for better processing and recaping student’s grade.